Estimation of Syphilis Serostatus on the Safety of Infertile Patients (Medico Legal Update, 2021)
Background: Infertility is a case assuming approximately 15 percent of couples in the world. At Italy, theevaluated percentage increases to 20 percent. There are many reasons for this case, among that a significantfunction appears to be manipulated by infections of the genital tract.Aim of the Study: For assessments the influence of syphilis on the safety of infertile patients.Materials and Method: All specimens of serum were initial evaluated utilizing a non–Treponema pallidumserologic(Ag) analysis to estimated for syphilis disease, & then a Treponema pallidum serologic (Ag)analysis was proceed to assert the positive specimen of syphilis recognized via the checking test.Results: a total of 137 cases of infertile patients were collected (83 cases in male, 54 cases in female), from83 cases of infertile male founded that 20 cases were suspected to T. pallidum infection while from 54 caseof infertile female were founded that 15 cases were suspected to infection with Treponema pallidum bacteria.Also these results show that patients with continuous infertility have significant level of T. palliduminfemales with age 41-50 years (54.55) while males with age 31- 40 years (34.62) than the age suspected forT. pallidum is > or = 41 years.Conclusions: A positive date of syphilis contagion may decrease the average of clinical gestation by sexualcontact. Also, this decreasing in the average of clinical gestation needs a diversity of agents, includingdensity of endometrial, grown oocytes number, the number of pollinated, splited oocytes under normalconditions, & the average of implantation.